1953
DOI: 10.1029/tr034i003p00427
|View full text |Cite
|
Sign up to set email alerts
|

A method of forecasting low flow of streams

Abstract: This paper presents a method of forecasting the discharge of streams during periods of low flow by use of the normal base‐flow depletion curve and frequency curves of runoff from concurrent precipitation and snow melt. Base flow from antecedent precipitation, together with runoff from concurrent precipitation and snow melt, constitutes the total runoff. The base flow resulting from antecedent precipitation may be projected several weeks or, in some cases, months into the future. The added runoff from subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1959
1959
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…The normal base-flow recession curves at Cathedral Peak can therefore be accepted to represent conditions throughout the year. Riggs (1953) found that the base-flow recession curves for many tributaries of the Columbia River show marked differences between winter and summer recessions, while others may be represented by single curves applicable throughout the year.…”
Section: Base-flow Recession Theorymentioning
confidence: 96%
See 2 more Smart Citations
“…The normal base-flow recession curves at Cathedral Peak can therefore be accepted to represent conditions throughout the year. Riggs (1953) found that the base-flow recession curves for many tributaries of the Columbia River show marked differences between winter and summer recessions, while others may be represented by single curves applicable throughout the year.…”
Section: Base-flow Recession Theorymentioning
confidence: 96%
“…This is the normal groundwater depletion curve of Horton (1935), Snyder (1939, Wicht (1942), Hydrology Handbook (1949), Grundy (1951), the mean or normal depletion curve of Johnstone and Cross (1949), the ground-water recession curve of Foster (1948), the perennial ground-water curve of Troxell (1953), the normal base-flow depletion curve of Riggs (1953) and the "Mittlere TrockenwetterAuslauflinie" of Schaffernak (1935).…”
Section: Mechanical Construction Of Baseflow Recession Curves From Cmentioning
confidence: 98%
See 1 more Smart Citation
“…10) includes many periods of declining discharge when the trend approaches a straight line on a semilog graph, similar to those for Devils River near Juno and for' Goodenough Springs. These parallel straight lines represent the rate of depletion of the ground-water reservoir, that is, the base flow, during periods of little or no rainfall (Riggs, 1953;Troxell, 1953). Where the recession is a straight line on a semilogarithmic projection, the following formula may be used:…”
Section: Devils Rivermentioning
confidence: 99%
“…In spite of early attempts to develop models for applications on low flows (Riggs, 1953;Bernier, 1964;Popov, 1964;Singh and Stall, 1971;Larras, 1972;Oberlin and Michel, 1978), low-flow forecasting has received only limited attention in the literature compared to flood forecasting (see e.g. reviews by Cloke and Pappenberger, 2009;Hapuarachchi et al, 2011).…”
Section: P Nicolle Et Al: Benchmarking Hydrological Models For Low-mentioning
confidence: 99%